Economy and sustainability: how economic integration stimulates stringent environmental regulations - Tosun, Jale; Knill, Christoph (Sustainability, 2009)
The interaction between economic integration and environmental policy has become an important issue in the last few years. Despite the considerable scholarly attention this topic attracted, actual government responses in terms of environmental policy outputs remain largely untouched by both theoretical and empirical work. To fill this gap, we suggest a theory-based disaggregation of the compound variable economic integration for deriving more precise expectations on its differential impact on environmental policy arrangements. In doing so, we show that economic integration may indeed trigger the promulgation of more demanding environmental regulations. To illustrate our arguments empirically, we analyze the development of Turkish clean air policy between 1975 and 2005.